Saikosaponin d Alleviates Liver Fibrosis by Negatively Regulating the ROS/NLRP3 Inflammasome Through Activating the ERβ Pathway - Zhang, Kehui; Lin, Liubing; Zhu, Yingying; Zhang, Na; Zhou, Meng’en; Li, Yong (Frontiers in Pharmacology, 2022)
Saikosaponin d (SSd) has a steroidal structure and significant anti-inflammatory effects. The purpose of this study was to explore the mechanism underlying SSd’s inhibitory effects on liver fibrosis. Methods: Wild-type and estrogen receptor knockout (ERKO) mice were treated with CCl4 to establish liver fibrosis mouse models. The effects of SSd on hepatic fibrogenesis were studied in these mouse models. Hepatic stellate cells (HSCs) were activated by H2O2 to investigate the potential molecular mechanisms. The establishment of the models and the degrees of inflammation and liver tissue fibrosis were evaluated by detecting changes in serum liver enzymes and liver histopathology. The expression of α-SMA and TGF-β1 was determined by immunohistochemistry. The expression and significance of NLRP3 inflammasome proteins were explored by RT-PCR and Western blotting analyses. The mitochondrial ROS-related indexes were evaluated by MitoSOX Red. Results: Fibrous hyperplasia, infiltration of inflammatory cells and fat, and deposition of collagen in the vessel wall of portal area were observed in the liver of wild-type and ERKO mice treated with CCL4. The expression levels of α-SMA and TGF-β1 in the vascular wall and portal area were obviously increased. SSd treatment significantly reduced the degree of fibrosis in wild-type and αERKO mice, but not in βERKO mice. Compared with untreated mice, treatment with SSd significantly downregulated the mRNA and protein levels of NLRP3 inflammatory and fibrosis-related indicators in wild-type and αERKO mice, but not in βERKO mice. Conclusion: SSd alleviated liver fibrosis by negatively regulating the ROS/NLRP3 inflammasome through activating the ERβ pathway.